Items found in a doctor's medical bag, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 2-9-64 p. A3.
Items found in a doctor's medical bag, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth